2005
DOI: 10.2334/josnusd.47.53
|View full text |Cite
|
Sign up to set email alerts
|

A marker of oxidative stress in saliva: association with periodontally-involved teeth of a hopeless prognosis

Abstract: The aim of this study was to determine the association between levels of a marker of oxidative stress, 8-hydroxydeoxyguanosine (8-OHdG), in saliva and the presence of teeth with a hopeless prognosis as a result of advanced periodontitis. Thirty-four periodontitis patients were divided into two groups based on the presence or absence of periodontally-involved teeth of hopeless prognosis. Salivary levels of 8-OHdG in those with were significantly higher than in subjects without periodontally-involved teeth of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
73
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 39 publications
13
73
3
Order By: Relevance
“…Our study showed that the salivary 8-OHdG levels were significantly higher in the periodontitis patients than in the healthy controls. This result confirms findings of limited previous studies (Sawamoto et al 2005;Takane et al 2005;Takane et al 2002). Also, we detected the 5-kbp mtDNA deletion in the gingival tissues of 20 of the 32 periodontitis patients and did not detect the 7-kbp mtDNA deletion in the periodontitis patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed that the salivary 8-OHdG levels were significantly higher in the periodontitis patients than in the healthy controls. This result confirms findings of limited previous studies (Sawamoto et al 2005;Takane et al 2005;Takane et al 2002). Also, we detected the 5-kbp mtDNA deletion in the gingival tissues of 20 of the 32 periodontitis patients and did not detect the 7-kbp mtDNA deletion in the periodontitis patients.…”
Section: Discussionsupporting
confidence: 92%
“…However, information on markers of ROS reactions with DNA in periodontitis is limited. The majority of published data on oxidative damage to DNA has been reported by a Japanese group who investigated 8-OHdG levels in the saliva of periodontitis patients (Sawamoto et al 2005;Takane et al 2005;Takane et al 2002). Their studies demonstrated that salivary levels of 8-OHdG in samples from subjects with CP were significantly higher than those from periodontally healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we evaluated the levels of 8-OHdG [36] and HEL [20], which are both oxidative stress markers, in whole saliva as biomarkers in clinically healthy individuals (Group 1). Both 8-OHdG and HEL decreased significantly after LDOA of CaIFN-4 In Group 1, 4 of 5 dogs tested positive for occult blood, but this rate decreased during LDOA of CaIFN-4 (data not shown), possibly reflecting stress levels.…”
Section: Discussionmentioning
confidence: 99%
“…The saliva samples of the dogs in Group 1 were centrifuged at 10,000  g for 10 min, and the supernatant was used to determine 8-hydroxydeoxyguanosine (8-OHdG) and N-(Hexanoyl) Lysine (HEL) levels as oxidative stress biomarkers [36,20] with enzyme-linked immunosorbent assay (ELISA) kits (Japan Institute for the Control of Aging, Nikken SEIL Corporation, Fukuroi, Shizuoka, Japan).…”
Section: Determination Of Salivary 8-hydroxydeoxyguanosine and N-(hementioning
confidence: 99%
“…One study reported high 8-OHdG levels in whole saliva and GCF of patients with CP in a Japanese population, but systemic levels of 8-OHdG were not measured. 42 However, GCF levels of 8-OHdG were suggested as a biomarker for DNA damage caused by oxidative stress and an indicator for CP severity. 43 Konopka et al 44 showed that 8-OHdG levels in Figure 4 In response to ligature-biofilms, nuclear factor erythroid 2-related factor 2 (Nrf2 À/À ) mice develop severe bone and attachment loss associated with high oxidative stress.…”
Section: Nrf2 Down-regulation In Periodontitismentioning
confidence: 99%